Hydration and exercise - Davies, T. (2009)
Good hydration at any level of exercise participation is important in preventing unnecessary cardiovascular stress as well as many of the other side effects of dehydration such as nausea, vomiting, headaches and sluggishness. It is particularly important in hot and humid weather when sweat loss is much greater. Most of us do not consume enough fluid on a daily basis and therefore spend much of our lives in a permanent state of dehydration, albeit a relatively minor one, and with little noticeable effect on our lives other than the odd headache or feeling of lethargy. However add physical activity to the equation and good hydration becomes essential to staying healthy and at elite levels, particularly in endurance related sport, it could mean the difference between winning and losing.